The Long-Term Mental Health Consequences of Torture, Loss, and Insecurity: A Qualitative Study Among Survivors of Armed Conflict in the Dang District of Nepal - Kienzler, Hanna; Sapkota, Ram P. (Frontiers in Psychiatry, 2020)
Nepal has witnessed several periods of organized violence since its beginnings as a sovereign nation. Most recently, during the decade-long Maoist Conflict (1996-2006), armed forces used excessive violence, including torture, resulting in deaths and disappearances. Moreover, there is widespread gender-, ethnic- and caste-based discrimination, and grossly unequal distribution of wealth in the country. While the immediate mental health effects of the conflict are well studied, less is known about the ways Nepalese survivors perceive their mental health problems, seek help and respond to mental health treatment in the long-term. This research project begins to provide insight into these complexities. Semi-structured interviews were carried out with 25 people (14 men, 11 women) aged 30 to 65 in Dang district in 2013. To elicit illness narratives, a translated and culturally adapted version of the McGill Illness Narrative Interview (MINI) was used. Additionally, participants were interviewed about their war experiences and present-day economic and social situations. The transcripts were coded using deductive and inductive approaches and analyzed through thematic analysis. The study provides insight into temporal narratives of illness experience; salient prototypes regarding current health problems; and explanatory models, including labels, causal attributions, treatment expectations, course, and outcome. It also explores help- and health-seeking behaviour and pathways to care. Symptoms were found to be widespread and varied, and were not solely attributed to violent experiences and memories, but also to everyday stressors related to survivors’ economic, social, and familial situations. In order to ease their physical and emotional pain and socioeconomic pressures, participants resorted to coping strategies such as social activities, avoidance, withdrawal, and substance use. Many participants had received biomedical treatment for their psychosocial problems from doctors and specialists working in public and private sector clinics and hospitals as well as different forms of traditional healing. These results shed light on the long-term impact of the Nepalese conflict on survivors of extreme violence, highlighting local explanatory models and help- and health-seeking behaviours. These findings inspire recommendations made for the development of appropriate and holistic psychosocial interventions focusing on well-being, social determinants of health, and human rights.